The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.3791/2655
|View full text |Cite
|
Sign up to set email alerts
|

Organotypic Culture of Full-thickness Adult Porcine Retina

Abstract: There is a recognized demand for in vitro models that can replace or reduce animal experiments. Porcine retina has a similar neuronal structure to human retina and is therefore a valuable species for studying mechanisms of human retinal injury and degenerative disease. Here we describe a cost-effective technique for organotypic culture of adult porcine retina isolated from eyes obtained from an abattoir. After removing the anterior segment, a trephine blade was used to create multiple neural retina-Bruch's mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 9 publications
(1 reference statement)
0
20
0
Order By: Relevance
“…In contrast, the explants cultured with the inner retina in contact with the membrane displayed better maintenance of the retinal laminar microarchitecture and significant attenuation of photoreceptor and ganglion cell death over time. Another study, by Wang et al [2011], described a nonconventional method to explant adult porcine retinas onto sterile filter paper, and it was found that retinal morphology and phenotype were wellpreserved for up to 7 days in culture. Moreover, retina explants have always been maintained at an air-liquid interface, except for the study by Wang et al [2011] in which the explant/filter paper unit was completely immersed in the cell culture medium.…”
Section: Orientation Of Cultured Retina Explantsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, the explants cultured with the inner retina in contact with the membrane displayed better maintenance of the retinal laminar microarchitecture and significant attenuation of photoreceptor and ganglion cell death over time. Another study, by Wang et al [2011], described a nonconventional method to explant adult porcine retinas onto sterile filter paper, and it was found that retinal morphology and phenotype were wellpreserved for up to 7 days in culture. Moreover, retina explants have always been maintained at an air-liquid interface, except for the study by Wang et al [2011] in which the explant/filter paper unit was completely immersed in the cell culture medium.…”
Section: Orientation Of Cultured Retina Explantsmentioning
confidence: 99%
“…Common PC inserts described in the literature come in 2 general formats: standing inserts (e.g., Millicell inserts from Milipore) or hanging inserts such as Corning's Transwell inserts. In addition to standard cell culture inserts, Wang et al [2011] built a custom-made stand using the base of a 5-mL-pipette tip to allow the circulation of culture medium to both sides of the retina. Koizumi et al [2007] also described a rabbit retina organotypic culture system, in which the oxygen supply for photoreceptors was ameliorated by raising the height of the culture insert using a custom-made stand (2 cm in diameter and 1 cm high) made from a 1-mL Monoject tuberculin syringe with agitation.…”
Section: Types Of Cell Culture Inserts Usedmentioning
confidence: 99%
See 3 more Smart Citations